Rhabdomyosarcoma in Uterine Cervix: A 30-Year-Old Tunisian Woman Case Report - Boudhina, Emna; Mousli, Alia; Lasmar, Ines; Bouguerra, Fadoua; Zenzri, Yosr; Abidi, Rim; Nasr, Chiraz; Mezlini, Amel (Reports of Radiotherapy and Oncology, 2023)
Introduction: Rhabdomyosarcoma (RMS) is a rare and aggressive mesenchymal tumor arising from skeletal muscle cells. Although it is predominantly seen in children, it can also affect adults. RMS typically presents as a rapidly growing mass in the head and neck region, genitourinary tract, or extremities. Among these sites, cervical RMS is exceedingly rare and has only been reported in a handful of cases. Case Presentation: In this report, we present a case of cervical RMS in a 30-year-old woman diagnosed and treated at the Salah Azaiez Institute. We describe the clinical presentation, imaging findings, histopathological characteristics, and treatment modalities used in this patient’s management. Additionally, we review the existing literature on cervical RMS to highlight the rarity of this entity and the challenges in its diagnosis and management. A 30-year-old woman with no pathological history suddenly presented with a cervical polyp with no other symptoms. On gynecological examination, a polypoid mass measuring 3 cm developed in the lower lip of the cervix. A surgery consisting of the cervical polyp removal was performed, showing at macroscopy several polypoid fragments measuring up to 1.5 cm, microscopically non-characterizable. Gynecologists opted for conization. Definitive histology concluded with an embryonic RMS with spindle cells (desmin+, myogenin+) of the uterine cervix with microscopically involved margins, resulting in the amputation of the whole cervix. The pelvic MRI showed no residual mass. The PET-CT did not find any hypermetabolic site. The tumor was classified as IA IRSG (Intergroup Rhabdomyosarcoma Study Group) favorable group (T1a according to the TNM classification), corresponding to the low risk of recurrence subgroup. Multidisciplinary reunion decided to treat with adjuvant chemotherapy based on 4 cycles of Doxorubicin and Ifosfamide and did not retain the indication of postoperative radiation therapy. Conclusions: Given the rarity of RMS in adults and the absence of standardized protocols for managing these tumors, a multidisciplinary decision is essential, and case reports remain highly relevant.